1994
DOI: 10.1248/bpb.17.509
|View full text |Cite
|
Sign up to set email alerts
|

Malonylginsenoside Rb1 Potentiates Nerve Growth Factor (NGF)-Induced Neurite Outgrowth of Cultured Chick Embryonic Dorsal Root Ganglia.

Abstract: Effects of malonylginsenoside Rb1 (GRb1-m) isolated from dried root of Panax ginseng C. A. Meyer (Araliaceae) on neuronal survival and neurite outgrowth were compared with those of ginsenoside Rb1 (GRb1) using organ culture of chick embryonic dorsal root ganglia (DRG) and cell culture of DRG neurons. In the organ culture, nerve growth factor (NGF) showed neurite outgrowth promoting effect. GRb1-m (30 microM) significantly potentiated this NGF-induced neurite outgrowth with similar potency to that of GRb1 (30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…In addition, significant improvement in learning and memory has been observed in brain-damaged rats (Zhao and McDaniel, 1998;Zhong et al, 2000) and aged rats (Zhong et al, 2000) after oral administration of ginseng powder, and the major ginseng saponins, ginsenoside Rb 1 and Rg 1 , are known to improve spatial learning in normal mice (Mook-Jung et al, 2001). With respect to their effects on neuronal cells, it has been shown that neurite outgrowth of rat cultured cerebral cortical neurons is enhanced by crude ginseng saponins (Sugaya et al, 1988), and that ginsenoside Rb 1 potentiates the nerve growth factor (NGF)-mediated neurite outgrowth of chick dorsal root ganglia (Saito et al, 1977;Nishiyama et al, 1994). We have previously studied the neurite outgrowth activity of methanol extracts from seven kinds of Ginseng drugs and 19 constituents isolated from YeSanchi (rhizome of Panax vietnamensis HA et GRUSHV.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant improvement in learning and memory has been observed in brain-damaged rats (Zhao and McDaniel, 1998;Zhong et al, 2000) and aged rats (Zhong et al, 2000) after oral administration of ginseng powder, and the major ginseng saponins, ginsenoside Rb 1 and Rg 1 , are known to improve spatial learning in normal mice (Mook-Jung et al, 2001). With respect to their effects on neuronal cells, it has been shown that neurite outgrowth of rat cultured cerebral cortical neurons is enhanced by crude ginseng saponins (Sugaya et al, 1988), and that ginsenoside Rb 1 potentiates the nerve growth factor (NGF)-mediated neurite outgrowth of chick dorsal root ganglia (Saito et al, 1977;Nishiyama et al, 1994). We have previously studied the neurite outgrowth activity of methanol extracts from seven kinds of Ginseng drugs and 19 constituents isolated from YeSanchi (rhizome of Panax vietnamensis HA et GRUSHV.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside Rh2 recovers the scopolamine-induced reduction in long-term potentiation (LTP) in the hippocampal CA1 area [25]. Rb1 enhances the stimulatory effect of neurite outgrowth [26], promotes neurotransmitter release by modulating phosphorylation of synapsins through a cAMP-dependent protein kinase pathway [27], upregulates cell genesis in the dentate gyrus (DG) and CA3 hippocampal subregions [28]. Traditionally, two types of ginseng have been used: white ginseng, which is air-dried ginseng, and red ginseng, which is produced by steaming raw ginseng at 98-100 °C for 2-3 h [29].…”
Section: Panax Ginsengmentioning
confidence: 99%
“…C. officinale has been shown to improve memory in scopolamine-injected mice [101]. Several formulations containing C. officinale have been showed to improve memory impairment in cerebral ischemia [102,103], Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) -injected mice [104] and Tg-APPswe/PS1dE9, transgenic mice of AD [105].…”
Section: Miscellaneous Tkm Plantsmentioning
confidence: 99%
“…However, this study did not clarify which component within the crude saponin extract of ginseng roots played the most significant role. Later studies screened out ginsenoside Rb1, Rb3, notoginsenosideR4 and Fa as the active compounds that caused the outgrowth and maturation of neurites and they could possibly recover the function of degenerated brains (Nishiyama, Cho, Kitagawa, & Saito, 1994;Tohda, N. Matsumoto, Zou, Meselhy, & Komatsu, 2002). Zukomei-to (ZMT, or Xu Ming Tan in Chinese), composed of traditional Chinese and Japanese herbal drugs, has long been used in treating postapopletic sequelae, clinically indicating that it might reactivate neuronal function in degenerated neuronal circuits.…”
Section: Herbal Medicines Able To Restore Neuroplasticity In Some Cnsmentioning
confidence: 99%
“…Malonylginsenoside Rb1 (GRb1-m) extracted from dried root of Panax ginseng C.A. Meyer and ginsenoside Rb1 had a synergizing effect on NGF (Nishiyama et al, 1994). They potentiated the effect of NGF on promoting the neurite outgrowth, eliminating the glial cells when they are co-cultured with neurons, and prolonging the duration of neuronal survival.…”
Section: Increase In the Expression Of Growth Factorsmentioning
confidence: 99%